Pertumbuhan Tanaman Ginseng Jawa (Talinum paniculatum Gaertn) yang Dipengaruhi Volume Penyiraman - Intan Nurcahya; Visi Tinta Manik; Nahiqal Ilham Matira; Dedi Natawijaya; Tini Sudartini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
Javanese ginseng (Talinum paniculatum Gaertn) is one of the medicinal plants which its roots (tubers) and leaves can be used as a medicine. The productivity of javanese ginseng is influenced by the availability of water. The purpose of this study was to determine the growth of javanese ginseng under the differences of watering volume. Watering volume treatment consisted of 7 treatments with 4 replications using a Randomized Block Design (RBD). Watering volume treatment consisted of 80% of field capacity (control), 50% of field capacity, 60% of field capacity, 70% of field capacity, 90 of field capacity, 100% of field capacity and 110% of field capacity. Watering volume treatment on javanese ginseng gave significantly different effect on plant height, number of leaves, root length, wet weight, and chlorophyll content, while the insignificant difference was shown in the number of stomata and relative moisture content. The best growth for plant height, number of leaves, root length, wet weight and chlorophyll content of javanese ginseng was shown in the treatment of watering volume of 50% of field capacity.